Economic crisis and well-being in Italy - Stanzani, Sandro (Italian Sociological Review, 2012)
Literature about the consequences of economic crisis on people’s well-being has highlighted some statistical connections. In particular, researchers agree on the fact that economic crises bring an increase in suicides, states of psychological depression, and abuse of alcohol along with them. This work deals with the issue of human impact of economic crisis, and, through a panel of data concerning Italian population, it searches for any possible connection with less critical but anyway significant phenomena, such as the general state of well-being and subjectively perceived health.